Topics in finite and discrete mathematics - Ross, Sheldon M. (Cambridge University Press, 2000)
Written for a broad audience of students in mathematics, computer science, operations research, statistics, and engineering, this textbook presents a survey of non-calculus topics in applied mathematics. Coverage includes probability, statistics, finance, graphs, linear programming, algorithms, and groups. Features an abundance of examples not normally found in finite mathematics courses.